Jordan Energy Sector Choices and Challenges - Malek Khalaf Albezuirat; Falah Mustafa Al-Saraireh; Muhammad Iqbal Hussain; Rosmaini Ahmad (SEISENSE (PRIVATE) LIMITED, 2018)
Energy is the lifeline for the whole of the service and industry sector in any country. Any imbalance in the energy sector is reflected on other sectors and the standard of living in the country. Energy problems are one of the most complex challenges facing governments. Especially in countries that rely on external energy sources. This situation is increased complexity by the presence of immediate changes in international relations and in fuel prices. Jordan is among the countries that depend on foreign energy sources and is located in the most volatile regions of the world in middle of the Middle East. Jordan is suffering from a permanent energy crisis that needs solutions which are compatible with many factors that may affect energy choices and decisions and alternatives available to get out of this crisis. Therefore, this study will attempt to focus on the Jordanian situation and identify the challenges and available choices. A comparison will be made of the available alternatives through Analytical Hierarchical Process (AHP). The results show that the priority of the energy solutions is to expand the mining of uranium and shale as well as to expand the construction of renewable power plants, as well as maintenance and modernization of existing plants and the establishment of new refineries.